Efficacy of COVID convalescent plasma therapy in hospitalized moderate coronavirus disease 2019 patients - Cosphiadi Irawan; Cleopas Martin Rumende; Lugyanti Sukrisman; Ceva Wicaksono Pitoyo; Suhendro Suwarto; Adityo Susilo; Nadia Ayu Mulansari; Alvin Tagor Harahap; Dimas Priantono; Ria Syafitri; Saptuti Chunaeni; Ni Ken Ritchie (Journal of Infection in Developing Countries)
Introduction: Covid Convalescent Plasma (CCP) failed to demonstrate its efficacy in severe and life-threatening coronavirus disease 2019 (COVID-19) cases. However, the role of CCP in hospitalized moderate cases is unclear. This study aims to examine the efficacy of administering CCP to hospitalized moderate coronavirus disease 2019 patients.